Pro-Poorness of Child’s Multidimensional Welfare in South Africa Using the Alkire-Foster and Fuzzy Sets Approaches - Oyekale, Abayomi; Molelekoa, Thonaeng Charity (Acta Universitatis Danubius. Œconomica, 2023)
The multidimensional notion of poverty has been widely emphasized in development economic literature. However, very little is known on pro-poorness of children’s multidimensional welfare in South Africa. This study therefore analyzed multidimensional welfare indicators of South African children and their pro-poorness. The data were the General Household Survey (GHS) for 2017, 2018 and 2019. Child’s poverty indicators were computed with Alkire-Foster and fuzzy set approaches. These were transformed into multidimensional wealth indicators (MWIs) and analyzed using the pro-poor growth index (PPGI) and poverty equivalent growth rate (PEGR). The results revealed that the fuzzy MWI were pro-poor between 2017 and 2018 with PPGI of 1.33, 1.84 and 2.56 for poverty incidence, depth and severity, respectively, but only pro-poor for poverty incidence in 2018/2019 with PPGI of 1.714. The fuzzy MWIs were largely pro-poor among Black/African and White children and those who resided in traditional areas between 2017 and 2019. It was concluded that although interventions to reduce poverty in South Africa had shown some level of pro-poorness, multidimensional poverty is still high among children. Also, analysis of pro-poor growth with multidimensional approach is highly sensitive to the adopted welfare computation methodology.